Prospective Study of the Mental Health Consequences of Sexual Violence Among Women Living With HIV in Rural Uganda. (May 2016) - Tsai, Alexander C.; Wolfe, William R.; Kumbakumba, Elias; Kawuma, Annet; Hunt, Peter W.; Martin, Jeffrey N.; Bangsberg, David R.; Weiser, Sheri D.
The association between sexual violence and depression is well known, but the temporal aspects of the association have not been well established. We analyzed data from a cohort of 173 HIV-positive women in rural Uganda who were interviewed every 3 months for a median of 1.8 years of follow-up. The method of generalized estimating equations (GEE) was used to model the marginal expectation of depression symptom severity (Hopkins Symptom Checklist for Depression), mental health–related quality of life (MOS-HIV Mental Health Summary), and heavy drinking (Alcohol Use Disorders Identification Test) as a function of self-reported forced-sex victimization in the 3 months prior to interview. Estimates were adjusted for variables known to confound the association between victimization and mental health status. To assess any potential reciprocal relationships, we reversed the temporal ordering of the exposures and outcomes and refitted similar GEE models. In multivariable analyses, victimization was associated with greater depression symptom severity ( b = 0.17; 95% CI = [0.02, 0.33]) and lower mental health–related quality of life ( b = −5.65; 95% CI = [−9.34, −1.96]), as well as increased risks for probable depression (adjusted relative risk [ARR] = 1.58; 95% CI = [1.01, 2.49) and heavy drinking (ARR = 3.99; 95% CI = [1.84, 8.63]). We did not find strong evidence of a reciprocal relationship. Our findings suggest that forced sex is associated with adverse mental health outcomes among HIV-positive women in rural Uganda. Given the substantial mental health–related impacts of victimization, effective health sector responses are needed.